2006
DOI: 10.1159/000095588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Experimental Lung Injury from Acute Renal Failure with Injury due to Sepsis

Abstract: Background: Acute renal failure (ARF) and acute respiratory distress syndrome (ARDS) coexist frequently, and the mortality rate of this combination is very high. It is well established that cytokines and chemokines play a major role in the pathogenesis of ARDS. In addition, heat shock proteins (HSPs) have been shown to be protective against ARDS. Objectives: The purpose of this study was to investigate the pathophysiology of ARDS in two different conditions, sepsis and ARF. Methods: We examined five different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 62 publications
1
30
2
Order By: Relevance
“…The relationship between pulmonary failure and mortality has been evaluated extensively in studies of ARDS patients; however, experimental results differ considerably [24,25,26,27,28]. Esteban et al [28] determined that independent prognostic factors were coma, ARDS and sepsis in patients on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between pulmonary failure and mortality has been evaluated extensively in studies of ARDS patients; however, experimental results differ considerably [24,25,26,27,28]. Esteban et al [28] determined that independent prognostic factors were coma, ARDS and sepsis in patients on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that AM may also play a role in the development of secondary pulmonary disorders like acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) [16, 17]. Common causes of indirect lung injury leading to ALI and ARDS are extrapulmonary foci such as peritonitis, pancreatitis, trauma, massive transfusions, or major surgery [18,19,20,21,22]. However, the question of whether AM are affected by extrapulmonary infections or rather actively participate in the development of sepsis, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent peak airway pressure may still have been sufficient to cause an increase in alveolar epithelial permeability. In addition, ARDS caused by sepsis or acute renal failure [24] could make the lungs more susceptible to alveolar tearing compared with normal lungs subjected to injurious mechanical ventilation as in the study.…”
Section: Discussionmentioning
confidence: 99%